Scientific Reasoning, Critical Thinking, and Academic Performance in Science of Selected Filipino Senior High School Students - Mae F. Farillon, Leah (Utamax : Journal of Ultimate Research and Trends in Education, 2022)
This correlational study on quantitative in nature was conducted to determine the relationship of scientific reasoning skills, critical thinking skills, and performance in Science of senior high school (SHS) students at Tapaz National High School, Capiz, Philippines. The variables in this study are the six different strands in SHS, namely, Science, Technology, Engineering, and Mathematics (STEM); General Academic Strand (GAS); Accountancy, Business, and Management (ABM); Home Economics (HE); Information and Communications Technology (ICT); and Shielded Metal Arc Welding (SMAW). The study used three instruments to quantify its goal with the statistical tools used to analyse data, i.e. the mean, standard deviation, and Pearson's r correlation coefficient. All inferential tests were set at 0.05 alpha level. The findings of the study revealed that the level of scientific reasoning skills of SHS students when taken as a whole was "high", and when grouped according to strand, the STEM, GAS, ABM, HE, and ICT were "high" while the SMAW was on “average” level of critical thinking skills. While when taken as a whole is found "developed" and when grouped according to strand, the STEM, GAS, ABM, HE, and ICT are "developed" while the SMAW is "moderately developed"; and their level of performance in Science, when taken as a whole, is "very satisfactory" and when grouped according to strand, the STEM, GAS, ABM, and HE were "very satisfactory" while the ICT and SMAW are "satisfactory". A significant relationship among the variables was taken as a whole and grouped according to strand. Students should learn to engage in scientific argumentation to develop their scientific reasoning and critical thinking skills. Also, the teachers should build up certain students' skills to better their performance in Science and other subjects. The school administration should also look for more sustainable programs and workshops for the teachers and students to improve their studies and lives.